(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
It is of great importance to study the word in terms of its structure, to determine what parts it is made of. In this article, we tried to determine the structure, service and meanings of artistic terms used in simple terms in Uzbek and Karakalpak languages.